Mengupas Makna Kesetaraan Gender Dalam Perspektif R.A. Kartini Dan Pengaruhnya Bagi Pendidikan Perempuan Di Jawa Tahun 1891-1904 - Samijo, endarkusmiyati; Jurahman; Lestari, Siska Nurazizah; Kusmiyati, Endar (Universitas Nusantara PGRI Kediri, 2023)
This study aims to find out: (1) Assess and discuss the background of the life of R.A. Kartini, (2) Review and discuss the concept of gender equality R.A. Kartini in education, (3) to find out about the influence of R.A. Kartini on women's education in Java. The method used in writing this thesis is thehistorical method. The results of this study indicate that throughout civilization, women are very vulnerable to various forms of injustice. R.A. Kartini lived during a period whenfeudalism was still very strong, which eventually led to several problems that were considered crucial, for example, gender inequality. In addition, R.A.'s interest Kartini in fighting for education among thewider community is very big. He is aware of the backwardness of his people who still live in darkness,stupidity and powerlessness. The example of the struggle of R.A. Kartini's efforts to achieve genderequality included: establishing schools for women, communicating with Dutch society which ultimately became the basis of her struggle. Another thing that was championed by R.A. Kartini is about opposing polygamy and breaking ancient customs. R.A. Kartini also opposed the culture of seclusion and emphasized the importance of providing opportunities for women to further develop themselves. R.A.'sthoughts Kartini certainly had a major influence on the development of women's education in Java and throughout Indonesia, such as the revival of women's education in Java, the establishment of women'sschools, the increase in the dignity and status of women, and the emergence of new female figures.